Development of a functional neuromuscular stimulation (FNS) muscle training program to prepare paraplegics for standing - Schafer, Carol Linda (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Wheelchair-bound paraplegics are in an unnatural, almost all-day sitting position. This is physiologically disadvantageous as it may cause increased abdominal pressure, renal dysfunction, pressure sores, muscle atrophy and osteoporosis. Thus it would be beneficial, physiologically and psychologically, for a paraplegic to be able to stand for temporary periods of time. As a result of the muscle atrophy and functional degeneration that follows a spinal cord injury, it is essential for paraplegics to undergo a muscle restrengthening program, using Functional Neuromuscular Stimulation (FNS), before standing up under FNS control can be attempted. Six healthy spinal cord injured subjects with spinal lesions between CS and T9 (two tetraplegics and four paraplegics) exercised their quadriceps muscles at home using a portable two-channel FNS muscle stimulator. The muscles were exercised against an increasing load to maximise the training effect. Inclined standing exercise, under FNS control, was performed in the Inclistand. The subjects' general state of health and fitness were assessed, namely their responses during a maximal arm ergometry exercise test, arm muscle function, lung function, blood biochemistry and their dietary habits. Subjects have shown improvement in quadriceps muscle strength, fatigue resistance and muscle bulk to varying degrees - according to their individual circumstances. The tetraplegics responded in a different manner to that of the paraplegics. The muscle strength increased significantly by a mean (+SD) of 97,8 + 59,6% and 171,2 + 118,1% for the four paraplegics, left and right leg respectively. There was a mean improvement of 16% in fatigue resistance in the left leg (p=0,08), while the mean response of the right leg varied. Quadriceps muscle bulk increased by 4,43 + 3,4% (left) and 2,7 + 2,1% (right) (0,05<p<0,l). The amount of subcutaneous fat around the mid-thigh decreased significantly by 4,73 + 1,4% (left) and 3,43 + 1,1% (right leg). The group was in a state of general well-being, with the exception of one subject whose serum cholesterol concentration fell within the high risk category. This study therefore showed that the FNS was sucessful in improving the quadriceps muscle strength, bulk and fatigue response of the SCI people in our research group. The valuable experience gained from this FNS study will be used to improve the present program.